EXPLANATION
Considering the system of equations:
(1) 7x - 3y = -25
(2) 4x + 5 = y
Isolating x from the first equation:
Adding +3y to both sides:
7x = -25 + 3y
Dividing both sides by 7:
x = -25/7 + 3y / 7
Substituting x from (1) in (2):
4(-25/7 + 3y/7) + 5 = y
Applying the distributive property and removing the parentheses:
-100/7 + 12y/7 + 5 = y
Adding like terms:
-65/7 + 12y/7 = y
Subtracting -12y/7 to both sides:
-65/7 = y - 12y/7
Adding like terms:
-65/7 = -5y/7
Multiplying both sides by -7/5:
(-65/7)*(-7/5)= y
Switching sides:
y = (-65/7)*(-7/5)
Multiplying terms:
y= 13
Substituting y= 13 in (1):
x= -25/7 + 3*(13)/7
Multiplying like terms:
x= -25/7 + 39/7
Adding the fractions:
x= 2
The solution to the system of equations is:
(x,y) = (2,13)